2021
DOI: 10.1155/2021/6657017
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Simulation of Departure Passenger’s Behavior Based on an Improved Social Force Approach: A Case Study on an Airport Terminal in China

Abstract: The unprecedented growth of passenger throughput in large airport terminals highlights the importance of analyzing passengers’ movement to achieve airport terminal’s elaborate management. Based on the theory of original social force model, video data from a departure hall of a large airport terminal in China were analyzed to summarize passengers’ path planning characteristics. Then, a double-level model was established to describe passengers’ path planning behaviors. At the decision level of the proposed model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Zhang Yaping et al [3] analyzed the passenger behavior in the departure hall through video data analysis of an airport in China, and established a departure passenger path model by improving the social force model, which simulated the path planning behavior of passengers in the public pedestrian space and service facility selection area of the departure hall at an acceptable accuracy level.…”
Section: Related Workmentioning
confidence: 99%
“…Zhang Yaping et al [3] analyzed the passenger behavior in the departure hall through video data analysis of an airport in China, and established a departure passenger path model by improving the social force model, which simulated the path planning behavior of passengers in the public pedestrian space and service facility selection area of the departure hall at an acceptable accuracy level.…”
Section: Related Workmentioning
confidence: 99%
“…Soltani et al [ 9 ] used two software programs, Aimsun and Path Finder, to examine the service levels of pedestrian pathways and corridors at the Sadeghiyeh urban train station in Tehran, indicated the service levels of the main hall, north entrance, and south corridor of the station. Additionally, numerous scholars have made multiple achievements in areas such as simulating pedestrian behavior in subway stations [ 10 , 11 ], airport terminals [ 12 ], stairs [ 13 ], irregular channels (L [ 14 ], T [ 15 ], Y [ 16 ], Z [ 17 ]), and evacuation conditions [ 11 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is found that passenger flow density can be changed by taking economic or administrative measures. Zhang et al [8] built a improved social force model to simulate passengers' path-choice behaviors in departure halls, emphasizing that airport congestion caused by increasingly throughput and insufficient space capacity should be solved with flow path optimization.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, Social force model [21] and cellular automata model [22] are frequently adopted in microscopic simulation of pedestrian traffic, and the main differences between the two models are shown in Tab. Ⅱ [8]. Seeing that the flow line simulation model in transportation hubs requires high fidelity of pedestrian activities, the social force model is preferred in this paper [23].…”
Section: Introductionmentioning
confidence: 99%